2020
DOI: 10.1162/glep_a_00549
|View full text |Cite
|
Sign up to set email alerts
|

Political Economy Determinants of Carbon Pricing

Abstract: Carbon pricing is widely considered a key policy instrument for achieving substantial climate change mitigation. However, implementation remains patchy and price levels vary significantly across countries and regions. In this article, we analyze the structural social, political, and economic conditions under which carbon prices have been implemented so far. We estimate a Tobit regression model to investigate variations in explicit carbon prices over 262 national and subnational jurisdictions. Our results highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 56 publications
(65 reference statements)
0
23
0
9
Order By: Relevance
“…Empirical research has, for instance, revealed that perceptions of weak governance coincide with weaker climate policies (Rafaty 2018). Investigating the political economy of carbon pricing -including, specifically, emissions trading -another empirical study of 167 national and 95 subnational jurisdictions identified well-governed institutions as one of two conditions for successful implementation (Levi, Flachsland, and Jakob 2020). In particular, it found that three governance indicators -perception of corruption, lack of technical capacity, and the absence of independent institutions -affect the likelihood that a carbon price is adopted, and also have a bearing on the level of the carbon price in that jurisdiction.…”
Section: Why Governance Mattersmentioning
confidence: 99%
“…Empirical research has, for instance, revealed that perceptions of weak governance coincide with weaker climate policies (Rafaty 2018). Investigating the political economy of carbon pricing -including, specifically, emissions trading -another empirical study of 167 national and 95 subnational jurisdictions identified well-governed institutions as one of two conditions for successful implementation (Levi, Flachsland, and Jakob 2020). In particular, it found that three governance indicators -perception of corruption, lack of technical capacity, and the absence of independent institutions -affect the likelihood that a carbon price is adopted, and also have a bearing on the level of the carbon price in that jurisdiction.…”
Section: Why Governance Mattersmentioning
confidence: 99%
“…Deliberative learning processes could help to improve the outcome of government processes and increase trust in government decisions. Empirically, there is a significant positive correlation between trust in governments and the quality of institutions, on the one hand, and carbon price levels, on the other (Klenert et al 2018 ; Levi et al 2020 ).…”
Section: Pigouvian Pricing In the Wild: A Drama In Three Actsmentioning
confidence: 99%
“…Time remains a problem: Krausmann et al (2020) show that the majority of emissions comes from maintenance and use of infrastructures, leading to low price elasticity. Regulatory capacity also contributes to effective implementation (Levi et al, 2020). Moreover, carbon pricing may drive efficiency improvements and fuel switching but have a limited effect on decarbonization (J. F. Green, 2021).…”
Section: Insight 7 -Political Challenges Impede Effectiveness Of Carbon Pricingmentioning
confidence: 99%